Upaya perpustakaan sekolah inklusi dalam mengembangkan layanan perpustakaan yang ramah dan inklusif bagi siswa - Anjani, Marinda (Maliki Interdisciplinary Journal, 2025)
This research discusses the efforts of inclusive school libraries trying to make friendly and inclusive services for students with various backgrounds and different needs, aligning them to fulfill information needs without discriminating religion, culture, language. Libraries that support inclusive education must be created, and this was the main focus of the research. Some of the important steps identified include the training of librarians on the understanding of inclusive education and accessibility technologies; the provision of assistive technologies such as text readers and audiobooks; and the establishment of collaborative spaces that encourage social cooperation and interaction between students. The important role of parents also supports In addition, it is considered important that parents and teachers actively participate in the development of inclusive libraries. This is because cooperation between parents, teachers and librarians will strengthen inclusive education. A vibrant library relies on inclusion-based library programs, continuous evaluation and promotion of inclusion. this study highlights the role of the library as the most effective knowledge hub and social space to help students learn. The study also emphasizes that libraries should be used and evaluated regularly and are an important part of inclusive education plans in schools